Numerical Study of Hyper‐Thermic Laser Lipolysis With 1,064 nm Nd:YAG Laser in Human Subjects - Milanic, Matija; Muc, Blaz Tasic; Lukac, Nejc; Lukac, Matjaz (Lasers in surgery and medicine, 2019)
Background and Objectives The aim of this study was to develop a numerical model for hyperthermic laser lipolysis in human subjects to improve understanding of the procedure and find optimal therapeutic parameters. Study Design/Materials and Methods A numerical model of hyperthermic laser lipolysis (HTLL) on human subjects was developed that is based on light and heat transport, including the effects of blood perfusion and forced air cooling. Tissue damage was evaluated using the Arrhenius model. Three irradiation scenarios were considered: single skin area irradiation without and with forced air cooling, and sequential heating of four adjacent skin areas in a cyclical manner. An evaluation of the numerical model was made by comparing the recorded skin surface temperature evolution during an experimental HTLL procedure performed on the abdomen of ten human volunteers using a 1,064 nm Nd:YAG laser irradiation. Results A good agreement was obtained between the simulated skin surface temperatures and that as measured during the HTLL procedure. The temperature difference between the simulations and experiments was in the range of 0.2–0.4°C. The model parameters, which were fitted to the experiment were the perfusion parameter (0.36–0.79 and 0.18–0.49 kg/m 3·s for dermis and subcutis) and the subcutaneous tissue absorption coefficient (0.17–0.21 cm −1). By using the developed HTLL model and the determined parameters, temperature depth distributions and the resulting thermal injury to adipocytes were simulated under different treatment conditions. Optimal ranges of the HTTL treatment parameters were determined for different skin types, damaging adipocytes while preserving skin cells. The target subcutaneous temperatures were in the range of 43–47°C, which has been found to lead to programmed adipocyte death. The optimal treatment parameters were further used to define a range of recommended protocols for safe and effective multiarea cycled HTLL treatment of large body surfaces. Specifically, for the set of chosen optimal treatment parameters (4–5 treatment cycles, 1.2 W/cm 2 radiant exposure, and 60–130 W/cm 2 forced air heat‐transfer coefficient) the threshold surface temperature during irradiation was found to be in the range of 31–38°C, depending on the skin type and heat‐transfer coefficient. Conclusions The developed numerical model allows for the calculation of the temperature distribution and the resulting injury to adipocyte cells within deeper lying fatty tissues under different clinical treatment conditions. It is demonstrated that by measuring the temporal evolution of the skin surface temperature and by stopping the laser irradiation at predefined skin surface threshold temperatures, it may be possible to monitor and control the effects of the HTLL procedure deeper within the tissue. As such, the model provides a better insight into the HTLL, and may become a tool for defining the range of safe and effective HTLL treatment protocols for patients with different skin types. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.